Neonatal Clonazepam Administration Induced Long-Lasting Changes in GABAA and GABAB Receptors - Kubová, Hana; Bendová, Zdeňka; Moravcová, Simona; Pačesová, Dominika; Rocha, Luisa; Mareš, Pavel (International journal of molecular sciences, 2020)
Benzodiazepines (BZDs) are widely used in patients of all ages. Unlike adults, neonatal animals treated with BZDs exhibit a variety of behavioral deficits later in life; however, the mechanisms underlying these deficits are poorly understood. This study aims to examine whether administration of clonazepam (CZP; 1 mg/kg/day) in 7-11-day-old rats affects Gama aminobutyric acid (GABA)ergic receptors in both the short and long terms. Using RT-PCR and quantitative autoradiography, we examined the expression of the selected GABAA receptor subunits (α1, α2, α4, γ2, and δ) and the GABAB B2 subunit, and GABAA, benzodiazepine, and GABAB receptor binding 48 h, 1 week, and 2 months after treatment discontinuation. Within one week after CZP cessation, the expression of the α2 subunit was upregulated, whereas that of the δ subunit was downregulated in both the hippocampus and cortex. In the hippocampus, the α4 subunit was downregulated after the 2-month interval. Changes in receptor binding were highly dependent on the receptor type, the interval after treatment cessation, and the brain structure. GABAA receptor binding was increased in almost all of the brain structures after the 48-h interval. BZD-binding was decreased in many brain structures involved in the neuronal networks associated with emotional behavior, anxiety, and cognitive functions after the 2-month interval. Binding of the GABAB receptors changed depending on the interval and brain structure. Overall, the described changes may affect both synaptic development and functioning and may potentially cause behavioral impairment.
Keywords: mozek; GABAA/BZD receptor binding; receptory GABA-B; clonazepam; Protein Binding; Receptors, GABA-B; novorozená zvířata; krysa rodu Rattus; Hippocampus; potkani inbrední WF; Rats, Inbred WF; zvířata; hipokampus; Clonazepam; subunit mRNA expression; Animals, Newborn; benzodiazepiny; GABAB receptor binding; neonatal rat; Male; Brain; Benzodiazepines; vazba proteinů; receptory GABA-A; gamma-Aminobutyric Acid; Real-Time Polymerase Chain Reaction; GABA; Rats; klonazepam; Animals; mužské pohlaví; Receptors, GABA-A; kvantitativní polymerázová řetězová reakce